Spermiogenesis and spermatozoa ultrastructure in Salminus and Brycon, two primitive genera in Characidae (Teleostei : Ostariophysi : Characiformes) - Verissimo-Silveira, R.; Gusmao-Pompiani, P.; Vicentini, Carlos Alberto [UNESP]; Quagio-Grassiotto, I. (Wiley-Blackwell, 2006)
In Salminus, spermiogenesis is cystic and gives origin to a type I aquasperm. Spermatid differentiation is characterized by chromatin condensed into thick fibres, nuclear rotation, nuclear fossa formation, cytoplasmic channel formation, mitochondrial fusion producing long and ramified mitochondria, and the presence of several membranous concentric rings around the plasma membrane that encircles the cytoplasmic channel. In Salminus and Brycon, spermatozoa are very similar. They exhibit a spherical nucleus and chromatin condensed into fibre clusters, and a deep nuclear fossa. They show a long midpiece with few elongate mitochondria at the initial region and a cytoplasmic channel completely encircled by one or two membranous concentric rings. The flagellar axis is perpendicular to the nucleus and exhibits the classic axoneme (9 + 2). The very strong similarity observed between Salminus and Brycon spermatozoa supports the hypothesis that these subfamilies are likely to have a monophyletic origin.
Keywords: Characidae; Characiformes; spermatozoa; spermiogenesis; ultrastructure